PERIODE WAKTU PERGANTIAN CACING SUTERA DENGAN IKAN RUCAH SEBAGAI PAKAN BENIH IKAN GABUS (Channa striata) - Ari Setiawan; Yulisman .; Ade Dwi Sasanti (Universitas Sriwijaya, 2018)
ABSTRACT Silk worm is one of natural feeds for snakehead fry. The availability of silk worm could be a problem for snakehead culture in big scale. One of the solution is trash fish utilization to reduce silk worm. The purpose of this research was to determine the best of feeding period to replace silk worm with trash fish based on growth and feed efficiency of snakehead fry. This research was conducted on July until September 2015 in Laboratorium Dasar Perikanan, Program Study of Aquaculture, Faculty of Agriculture, University of Sriwijaya. The research was based on Completely Randomized Design (CRD) with five treatmens and three replications. The treatments are snakehead 21-51 days were fed by silk worm (P1), snakehead 21-41 days were fed by silk worm and 40-51 days by trash fish (P2), snakehead 21-36 days were fed by silk worm and 35-51 days by trash fish (P3), snakehead 21-31 days were fed by silk worm and 30-51 days by trash fish (P4), and snakehead 21-51 days were fed by trash fish (P5). The results showed that feeding period between silk worm and trash fish had no significant different on growth and feed efficiency of snakehead fry. The result indicated that trash fish can be utilized for feeding of snakehead fry age 21 until 51 days (P5). Water quality during the research were temperature 25-290C, ammonia 0.11-0.29 mg.L-1, dissolved oxygen 4.44-6.88 mg.L-1, and pH 5.3-7.2. Water quality parameters were still in good range for culture of Channa striata. Keywords : Snakehead, , Silk worm, Ttrash fish